The Effects of Cryptelytrops albolabris, Calloselasma rhodostoma and Daboia siamensis Venoms on Human Cancer Cells - Khunsap, Suchitra; Buranapraditkun, Supranee; Suntrarachun, Sunutcha; Puthong, Songchan; Khow, Orawan; Chulasugandha, Pannipa; Boonchang, Supatsorn (Asian Journal of Biological and Life Sciences, 2013)
Three snake venoms: Cryptelytrops albolabris, Calloselasma rhodostoma and Daboia siamensis were studied for cytotoxic activity and apoptosis on five cancer cell lines; BT474, SW620, KATO-III, Hep-G and ChaGo. Cytotoxic effect was determined by MTT assay and flow cytometry has 2 been used for apoptosis. Various concentrations of three venoms showed cytotoxic against cancer cells as time-dependent. The potent of cytotoxic from C. albolabris venom against cancer cells were: BT474 (2.96 ± 0.44 µg/ml), SW620 (3.32 ± 0.14 µg/ml), KATO-III (3.72 ± 0.11 µg/ml) and Hep-G (3.74 ± 0.43 µg/ml), respectively. C. rhodostoma venom showed cytotoxic to BT474 (3.16 ± 0.69 µg/ml), SW620 (3.5 ± 0.01 µg/ml) and KATO¬ 2 III (3.74 ± 0.37 µg/ml) while the venom of D. siamensis was highly toxic to only ChaGo (0.48 ± 0.04 µg/ml). Apoptotic cell death using PI staining was dose and time dependent.